Liquid crystal template-assisted electrodeposition of nanoporous nickel microspheres: A sensitive electrochemical sensing platform for electrocatalytic oxidation and quantitative determination of l-carnitine - R. Dehdari Vais; M. Negahdary; S.R. Rasouli Nasrabadi; A. Rahi; S.A. Dastgheib; H. Heli (Sensing and Bio-Sensing Research)
l-carnitine (LC) is a vital constituent of mammalian tissues, has a significant role in the function of different biological systems, and its determination is of great interest. Electrochemical sensing using nickelaceous nanostructured electrocatalysts offers potential interests and advantages. In the present study, nanoporous nickel microspheres (NNiMs) were electrodeposited and then utilized as an electrode modifier for the electrocatalytic oxidation and determination of LC. NNiMs were electrodeposited on a nickel substrate from a liquid crystal medium containing nickel (II) chloride, and Triton X-100 under a potentiostatic condition. The surface morphological characterization of the obtained nanoporous microspheres was followed by field emission scanning electron microscopy. NNiMs were transformed into the corresponding oxides by applying consecutive potential cycles in an alkaline medium, and the electron transfer coefficient and apparent charge transfer rate constant of the redox species present on the modified electrode surface were calculated as 0.59 and 0.54 s−1, respectively. Cyclic voltammetry, chronoamperometry, and steady-state polarization measurements were used for assessing the electrocatalytic oxidation mechanism and kinetics of LC on the NNiMs surface. Based on these measurements, an LC diffusion coefficient of 4.1 × 10−6 cm2 s−1, a catalytic rate constant of 4.0 × 104 cm3 mol−1 s−1, and an electron transfer coefficient of 0.41 were achieved. The proposed sensor was then employed as a sensitive amperometric sensor for determination of LC with a linear dynamic range of 25 to 217 μmol L−1, a calibration sensitivity of 67.85 mA L mol−1, and a detection limit of 3.2 μmol L−1. The designed sensing platform depicted a stable and reproducible response and insignificant interference from the common species found in the biological fluids and pharmaceutical formulations. Taking all these features together, the developed determination method can be satisfactorily exploited as a simple and quick tool for direct analysis of LC in pharmaceutical oral solutions and human serum samples.